Orthostatic intolerance and presyncopal states in young adults: The role of dehydration, lifestyle, academic stress and autonomic factors – a narrative review - Karol, Michał; Koseska, Kamila; Borowicz, Jan; Górecki, Bartosz; Kloch, Kinga; Romaniuk, Patryk; Lohin, Mariia-Khrystyna; Strawińska, Aleksandra; Bednarczyk, Małgorzata (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Orthostatic intolerance is an increasingly recognized disturbance of circulatory regulation in young adults, particularly in academic settings where characteristic lifestyle patterns promote autonomic imbalance. The aim of this narrative review is to synthesize current knowledge on pathophysiological mechanisms, classification, prevalence and management of orthostatic intolerance in young adults, with particular emphasis on the role of dehydration, sleep irregularities, academic stress and low physical activity. Description of the state of knowledge: Available data indicate that early haemodynamic changes after standing, including initial orthostatic hypotension and impaired baroreflex adaptation, are key mechanisms underlying presyncopal symptoms in this age group. In many patients complaints are misinterpreted as manifestations of anxiety or panic, which leads to delayed diagnosis, unnecessary cardiologic and neurologic investigations and failure to implement simple, effective lifestyle interventions. Studies in student populations show that recurrent presyncopal episodes, “brain fog” and exercise intolerance may significantly impair academic performance and quality of life, while remaining largely unreported. Summary (conclusions): Orthostatic intolerance in young adults rarely reflects severe structural disease but rather a mismatch between autonomic compensatory capacity and chronic environmental load. Early recognition, clear explanation of mechanisms and structured non-pharmacologic management focused on hydration, sleep hygiene, nutrition and physical activity usually lead to substantial symptom relief. In academic environments preventive measures and increased awareness among clinicians, students and university staff are essential to limit unnecessary diagnostics and to reduce the long-term functional impact of orthostatic intolerance.